The Impact of Supervisor Servant Leadership on Counselor Supervisee Burnout and Secondary Traumatic Stress - Colleen M Grunhaus; Thomas J. Ward; Victor E. Tuazon; Kristal James (Teaching and Supervision in Counseling, 2023)
This study investigates the prediction of supervisee burnout and secondary traumatic stress by perceived supervisor servant leadership. Authors hypothesized that the servant leadership of supervisors would predict diminished burnout and secondary traumatic stress of supervisees. A sample of 241 counseling supervisees participated in the cross-sectional study and completed instruments measuring burnout, secondary traumatic stress, and perceived servant leadership of their direct supervisors. Data were analyzed with two simple linear regressions, and a one-way MANOVA was performed to determine if supervisee burnout, supervisee secondary traumatic stress, and perceived servant leadership of supervisors differed significantly according to supervisor type (i.e., clinical, administrative, or dual role). Results confirmed the main hypothesis, and administrative supervisors were perceived to demonstrate significantly less servant leadership qualities than the other two supervisor types. Limitations, avenues for future research, and implications for counselor education and supervision are discussed.
Keywords: burnout; secondary traumatic stress; supervision; counselors; servant leadership